GAMBARAN TINGKAT PENGETAHUAN, SIKAP DAN PERILAKU TERHADAP PENCEGAHAN COVID-19 PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS BAITURRAHMAH ANGKATAN 2020 - Laura Zeffira; Seres Triola; Elfi Yulfienti; Elvi Fitraneti; Fitra Deny; Adilla Caseria Utari (Nusantara Hasana Journal, 2023)
The incidence rate of COVID-19 in Indonesia that still high, especially in medical school students at Baiturrahmah University Batch 2020 who registered few students infected by COVID-19, then need to do further research about the image of knowledge, manner, and behavior toward the covid-19 prevention so that it could give the education about procedures of preventing the spread of COVID-19, especially on the society particularly for students of Baiturrahmah University. This research to find out the image of knowledge, manner, and behavior level toward the covid-19 prevention in medical school students at Baiturrahmah University Batch 2020. This research's scope is the combination of virology, pulmonary disease science, and public health science. The research is held from March 2021 until January 2022. The type of this research is categorical descriptive. This research's accessible population is medical school students at Baiturrahmah University Batch 2020, with as many as 96 samples with simple random sampling technique. The univariate data analysis is displayed in frequency distribution and data processing using the computerized program SPSS version IBM 25.0. The most gender is female, which is 67 people (69,8%), most knowledge levels are good, which is 49 people (51,0%), most manners are good, which is 84 people (87,5%), and most behaviors are good which is 69 people (71,9%). The most gender is female with most knowledge levels are good, most manners are good, and most behaviors are good.